Managing Contemporary Security Challenges in Nigeria
XIX, 401 p. 9 illus., 7 illus. in color.
Keywords: This book covers a wide range of security issues in Nigeria, including insurgency, terrorism, herder-farmer conflicts, military reforms and internal security, the Nigeria Police Force and security management, intelligence gathering and insecurity, etc. It offers an in-depth assessment of the national security strategies and policies in Nigeria along with a critical assessment of the role of intelligence gathering in security management. It is useful for policymakers, students, and other important stakeholders in the security studies. Ali Arazeem Abdullahi is a Professor of Sociology at the University of Ilorin, Nigeria and a Senior Research Associate at the Department of Sociology, Faculty of Humanities, University of Johannesburg, South Africa. Usman A. Raheem, Ph.D. is a Professor of Geography in the Department of Geography and Environmental Management at the University of Ilorin, Nigeria. Jimoh Amzat is a Professor of Sociology at Usmanu Dan-Fodio University, Sokoto, Nigeria. He received the Erasmus Mundus scholarship by the European Union as a graduate student and and Georg Forster postdoctoral fellowship, Germany Kenneth C. Nwachukwu is a seasoned diplomat who served for 34 years in the nation’s foreign service; a career that saw him posted to various Nigerian Missions including Burkina Faso, Switzerland, Trinidad and Tobago, and was bookended as Nigeria’s Ambassador to Mali.